Hierarchical oxygen reduction reaction electrocatalysts based on FeSn0.5 species embedded in carbon nitride-graphene based supports. (1st August 2018) - Negro, Enrico; Nale, Angeloclaudio; Vezzù, Keti; Pagot, Gioele; Polizzi, Stefano; Bertoncello, Renzo; Ansaldo, Alberto; Prato, Mirko; Bonaccorso, Francesco; Rutkowska, Iwona A.; Kulesza, Pawel J.; Di Noto, Vito
Abstract: This work reports the synthesis, the physicochemical characterization and the electrochemical studies of new electrocatalysts (ECs) for the oxygen reduction reaction (ORR) that: (i) exhibit a hierarchical architecture; and (ii) do not comprise platinum. The active sites of the ECs consist of Fe and Sn species stabilized in " coordination nests " of a carbon nitride (CN) matrix. The latter exhibits a rough, microporous morphology and acts as a " shell " covering a graphene " core ". This paper: (i) discusses the role played by Fe as the " active metal " in this family of ECs; and (ii) examines in detail how the physicochemical properties and, correspondingly, the electrochemical performance are affected by a suitable activation procedureA meant to boost the ORR kinetics. The results lead to an improved fundamental understanding on the features of the active sites, including the impact of bothA and the pH of the environment in their performance and ORR mechanism. These insights clarify the most desirable features to be included in high-performing ECs belonging to this family, paving the way to the synthesis of next-generation, efficient ECs for the ORR that do not comprise platinum. Highlights: New " Pt-free " electrocatalysts (EC) for the oxygen reduction reaction (ORR) are devised. The hierarchical ECs comprise a graphene-based support " core " covered by a carbon nitride (CN) " shell ". The active sites are based on Fe and Sn species embedded in the CN " shell ". The interplay between the physicochemical properties and the ORR performance is elucidated.